Patterns of FDI in Southern European Periphery: a Tale of Missing FDI? - Laura Resmini (European Regional Science Association (ERSA), 2014)
This paper examines patterns of FDI inflows to Southern European (SE) regions, which seem to be at the margin of the FDI attraction game accounting for a very small share of total inward FDI in the EU. In order to understand why these regions attracted such a low number of foreign investors, this contribution provides the following analysis: i) an overall picture of the main characteristics of patterns of inward FDI in SE regions at geographical and sectoral level; ii) the factors that drive FDI flows into EU regions; iii) as assessment of the potential of attractiveness of SE regions, both in absolute terms and with respect to other EU regions. The main results indicate that SE regions are definitively less attractive than other EU regions, though a lot of variation does exist at both geographical and sectoral level. In order to improve their capacity to attract FDI SE regions should improve their factors of attractiveness by implementing several structural reforms
Keywords: F23; R12; C21; 330; foreign direct investment; Southern European periphery; spatial econometrics